Perfil epidemiológico das vítimas de acidente de motocicletas do estado do Ceará, referenciadas ao Instituto Doutor José Frota, de 2010 a 2013 - Linhares, Antonio Carlos Ferreira (2014)
To identify the epidemiological profile of motorcycle accident victims in the state of Ceará from 2010 to 2013, focusing on the direct costs. A cross-sectional study, developed in a tertiary hospital in Fortaleza. Male patients represent a prevalence of 86.5% in motorcycle accidents, however, female patients presented an increase of 188.9% in the period studied. The average hospital stay was of 13 days, with in-hospital cost of about R$ 1,486.02, on average. The costs with orthosis, prostheses and special materials (OPME) ranged from R$ 8.93 up to R$ 8.510.00, and in some cases, these costs were higher than medical care costs. Male patients represent the highest direct costs as well as a longer hospital stay. The high cost due to the use of OPME is not always determined by the severe injuries caused by the accident, but it is determined by the characteristics of the fractures caused by multisystem trauma.